Achieving Viability for Public Service Media in Challenging Settings (2020)
In the face of challenges posed by a shifting digital media landscape, an array of international bodies continue to endorse public service media (PSM) as an essential component of democratisation. Yet how can PSM achieve viability in settings where models of media independence and credibility are unfamiliar or rejected by political leaders? The answer lies in a holistic approach that is neither media-centric nor defeatist about PSM’s place in a landscape marked by younger generations’ widespread preference for social media platforms. There are more ways of working towards PSM than are often recognized. Wide-ranging research from media NGOs and academics demonstrates the potential of diverse, incremental approaches to embedding the values and mechanisms of PSM. These are as likely to involve regulatory and licensing institutions, unions of media practitioners, audiences, advocacy groups or social media platforms as content producers themselves. This Policy Brief considers the issues, research and policy options around achieving viability for PSM. It concludes with six recommendations that are relevant to policymakers, practitioners and media studies specialists.